Peers' Perceptions of the Environment and Learning Motivation Are Related to Science Learning Outcomes: Persepsi Lingkungan Teman Sebaya dan Motivasi Belajar Berhubungan dengan Hasil Belajar IPA - Fadilah, Qiroatul; Efendi, Nur (Indonesian Journal of Education Methods Development, 2025)
General Background : This study is grounded in the importance of psychological and social factors in determining students' academic success. Specific Background : The focus is to analyze the relationship between students' perceptions of the peer environment and learning motivation on the science learning outcomes of 8th-grade students at SMPN 1 Prambon. Knowledge Gap : Although previous studies have identified this relationship, an in-depth analysis within a specific context is needed to reveal potentially differing findings. Aims : This research aims to quantitatively describe the relationships among these variables. Results : The findings show a positive relationship between the peer environment and learning motivation with students’ learning outcomes. Novelty : The novelty of this study lies in the finding that students' perceptions of the peer environment do not entirely influence learning outcomes, which contradicts previous theories and suggests other, more dominant factors may be at play. Implications : These findings carry important implications for educators to consider other factors and design more comprehensive learning strategies, providing a basis for further research. Highlights : This research analyzes the relationship between peer environment, learning motivation, and science learning outcomes. The study used an ex-post facto method with a sample of 169 eighth-grade students. The results show a positive relationship between learning motivation and learning outcomes, but the peer environment's influence is not as direct as some theories suggest. Keywords : Student Perception, Learning Motivation, Learning Outcomes, Science, Ex-Post Facto